2018
DOI: 10.1038/s41598-018-23009-x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of plasma choline in acute coronary syndrome: importance of suitable sampling conditions for this assay

Abstract: Blood choline has been proposed as a predictor of acute coronary syndrome (ACS), however different testing procedures might affect the choline concentration because the lysophospholipase D activity of autotaxin (ATX) can convert lysophosphatidylcholine to lysophosphatidic acid (LPA) and choline in human blood. Although the influences of ATX on LPA levels are well known in vivo and in vitro, those on choline have not been elucidated. Therefore, we established suitable sampling conditions and evaluated the usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Certain AF-related GM features may be attractive candidates for detecting the disease at the self-terminating PAF. Moreover, many clinical studies have investigated the importance of choline as a biomarker for several human diseases, such as acute coronary syndrome (34)(35)(36)(37). The significant association between GM, choline, and atrial diameter (RASLD, LALRD, and LAAPD) has been identified in the current work.…”
Section: Discussionmentioning
confidence: 67%
“…Certain AF-related GM features may be attractive candidates for detecting the disease at the self-terminating PAF. Moreover, many clinical studies have investigated the importance of choline as a biomarker for several human diseases, such as acute coronary syndrome (34)(35)(36)(37). The significant association between GM, choline, and atrial diameter (RASLD, LALRD, and LAAPD) has been identified in the current work.…”
Section: Discussionmentioning
confidence: 67%
“…Concentrations of WBCho and PlCho increase during the early period of AMI, due to coronary plaque destabilization and stimulation of PLD by macrophages in tissue ischemia. Therefore, it has been suggested that cardiac ischemia can be detected early if choline levels of patients with ischemic symptoms are observed 52,53…”
Section: Resultsmentioning
confidence: 99%
“…Plasma choline level was measured using a fully automated colorimetric assay (Alfresa Pharma Corp., Osaka, Japan) 40 . Placenta samples were collected immediately after delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma choline level was measured using a fully automated colorimetric assay (Alfresa Pharma Corp., Osaka, Japan). 40 Placenta samples were collected immediately after delivery. Placenta samples measuring 2 cm × 2 cm × placenta depth (30-100 g) were collected from placental center while excluding amniotic membranes.…”
Section: Sample Collectionmentioning
confidence: 99%